2019
DOI: 10.3390/nu11112693
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Silverskin Extract: Nutritional Value, Safety and Effect on Key Biological Functions

Abstract: This study aimed to complete the scientific basis for the validation of a coffee silverskin extract (CSE) as a novel food ingredient according to European legislation. Nutritional value, safety, effects on biochemical biomarkers and excretion of short chain fatty acids (SCFAs) in vivo of CSE were assessed. Proteins, amino acids, fat, fatty acids, fiber, simple sugars and micronutrients were analyzed. For the first time, toxicological and physiological effects were evaluated in vivo by a repeated-dose study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 62 publications
(90 reference statements)
0
27
0
Order By: Relevance
“…CGA/g). Antioxidant properties of this extract at 1 mg/mL were also confirmed in human liver cells (HepG2) [ 24 ]. This extract may be a potential agent for the prevention of cellular damage induced by oxidative stress.…”
Section: Nutritional Value and Health Promoting Propertiesmentioning
confidence: 93%
See 2 more Smart Citations
“…CGA/g). Antioxidant properties of this extract at 1 mg/mL were also confirmed in human liver cells (HepG2) [ 24 ]. This extract may be a potential agent for the prevention of cellular damage induced by oxidative stress.…”
Section: Nutritional Value and Health Promoting Propertiesmentioning
confidence: 93%
“…CS preferentially supports bifidobacteria growth in vitro, suggesting that its consumption may have some prebiotic effects [ 35 ]. Studies carried out by our research group have shown the fiber fermentability of CSE in vivo [ 24 ]. Total short chain fatty acids (SCFAs) significantly increased ( p < 0.05) in feces of male Wistar rats treated with CSE (1 g/kg b.w.)…”
Section: Nutritional Value and Health Promoting Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The acute pro-motility effects of SCG demonstrated in that study could be influenced by short chain fatty acids (SCFAs), which have been shown to be released during SCGs fermentation by colon microbiota from medium and dark roasted coffee beans at concentrations higher than 10 mM [ 175 ], and SCFAs (10–200 mM) stimulate colonic motility [ 176 ]. Interestingly, an aqueous extract of coffee silverskin, another coffee by-product, may also display dietary fiber effect since total SCFAs derived from coffee silverskin extract fermentation were higher in feces of rats treated with the extract for 28 days [ 177 ]. Although its precise in vivo effects on gastrointestinal motility still needs to be determined, it might be related with the presence of melanoidins in it (see Section 3.5 ).…”
Section: Coffee and The Gastrointestinal Tract: Focus On Motor Funmentioning
confidence: 99%
“…In the concept of circular economy, the H. illucens larvae were reared on a basal substrate constituted by coffee roasting byproducts (coffee silverskin, Cs) supplemented with increasing percentages of microalgae ( Schizochytrium limacinum or Isochrysis galbana ) as the source of PUFAs such as docosahexaenoic, stearidonic, and α-linolenic acid [ 9 , 24 ]. On the other hand, Cs, rich in polyphenols and mainly composed of dietary fibers (≈55%), proteins (≈19%), carbohydrates (≈6%), and fat (≈2%), has been reported to have prebiotic and antioxidant activities [ 25 ].…”
Section: Introductionmentioning
confidence: 99%